1995
DOI: 10.1007/bf02536998
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate type and amount alter intravascular processing and catabolism of plasma lipoproteins in guinea pigs

Abstract: To test the effects of exchanging dietary complex and simple carbohydrate for fat calories on lipoprotein metabolism, guinea pigs were fed two different fat/carbohydrate ratios: 2.5:58% (w/w) or 25:29% (w/w) with either sucrose or starch as the carbohydrate source. Animals fed high-fat had higher plasma low-density lipoprotein (LDL) and hepatic cholesterol concentrations than animals fed low-fat diets (P < 0.01). The cholesteryl ester content per particle was higher, and the number of triacylglycerol (TAG) mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
1
12
3
Order By: Relevance
“…Accordingly, we found that LDL-C and VLDL-C increased upon high-fat feeding, regardless of dietary content of sucrose. This contradicts previous findings of a sucrose imposed elevation of TC and LDL-C when added to a high-fat diet in male guinea pigs [ 13 , 36 ]. The observed dissimilarity may be due to differences in dietary composition as the latter high-fat diets did not contain excess cholesterol [ 13 , 36 ] and/or a gender associated effect, as female rats—in contrast to males—proved resistant to sucrose-induced hypertriglyceridemia [ 37 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Accordingly, we found that LDL-C and VLDL-C increased upon high-fat feeding, regardless of dietary content of sucrose. This contradicts previous findings of a sucrose imposed elevation of TC and LDL-C when added to a high-fat diet in male guinea pigs [ 13 , 36 ]. The observed dissimilarity may be due to differences in dietary composition as the latter high-fat diets did not contain excess cholesterol [ 13 , 36 ] and/or a gender associated effect, as female rats—in contrast to males—proved resistant to sucrose-induced hypertriglyceridemia [ 37 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Although high fat compared with low fat, polyunsaturated compared with saturated fat, and rapeseed oil compared with olive oil increase LPL activity (Pawar & Tidwell, 1968;Jansen et al 1975;Weisenburg Delorme & Hams, 1975;Cryer et al 1978;Kiens et al 1987), plasma LDL levels are higher in the former and lower in the latter situation suggesting that the contribution of LPL activity to plasma LDL concentrations differs depending on the dietary treatment. For example, in guinea-pigs the increases in cardiac LPL induced by high fat intake have been associated with cholesteryl-esterenriched VLDL which are readily converted to LDL particles resulting in an expanded plasma LDL pool (Fernandez et al 1995). In contrast, the higher LPL activity with rapeseed oil intake observed in the present study might be related to an increased conversion of VLDL to smaller LDL particles which are rapidly cleared from plasma resulting in lower plasma LDL levels.…”
Section: L Fernandbz a N D Otherscontrasting
confidence: 66%
“…In guinea pigs, this is due to reduced amounts of triglyceride molecules in VLDL particles [23]. In mice, heparin-releasable [24,25] and adipose [6] lipoprotein lipase are increased.…”
Section: Discussionmentioning
confidence: 99%